Association of Single Nucleotide Polymorphisms in LEP, LEPR, and PPARG With Humoral Immune Response to Influenza Vaccine - Li, Mao; Wei, Hejiang; Zhong, Shuyi; Cheng, Yanhui; Wen, Simin; Wang, Dayan; Shu, Yuelong (Frontiers in Genetics, 2021)
Background: Although previous studies have proposed leptin plays an important role in energy metabolism as well as in immune response, the effects of leptin-related genes on influenza vaccine-induced immune response remain unexplored. In this study, we aimed to investigate the potential association of leptin gene (LEP), leptin receptor gene (LEPR) and peroxisome proliferator activated receptor gamma gene (PPARG) polymorphisms with humoral immune response to influenza vaccine. Methods: Based on the seroconversion to influenza vaccine, 227 low-responders and 365 responders were selected in this study, and 11 candidate single nucleotide polymorphisms (SNPs) were genotyped using the MassARRAY technology platform. Univariate and multivariate logistic regression analyses were used to explore the association of SNPs in LEP, LEPR and PPARG with humoral immune response to influenza vaccine. We also conducted a stratified analysis by gender to further clarify this association. The haplotypes analysis was performed using SNPStats. Results: Significant differences were observed in the genotypic distribution of PPARG rs17793951 between the two groups (P=0.001), and the PPARG rs17793951 AG+GG genotype was associated with a higher risk of low responsiveness to influenza vaccine adjusted for gender and age (additive genetic model: OR=2.94, 95% CI=1.67-5.19, dominant genetic model: OR=2.81, 95% CI=1.61-4.92). No significant association of other SNPs in LEP and LEPR with immune response to influenza vaccine was found. The stratified analysis found the gender difference in the association of LEPR and PPARG variants with immune response to influenza vaccine. We found that LEPR rs6673591 GA+AA genotype was correlated with low responsiveness to influenza vaccine only in males (OR=1.96, 95% CI=1.05-3.67), and PPARG rs17793951 AG+GG genotype was associated with low responsiveness to influenza vaccine in females (OR=3.28, 95% CI=1.61-6.67). Compared with the CGGAGGC haplotype composed of LEPR rs1327118, rs7602, rs1137101, rs1938489, rs6673591, rs1137100 and rs13306523, the CAAAAAC haplotype was positively correlated with immune response of influenza vaccine (OR=0.34, 95% CI=0.15-0.77). Haplotype TG comprised of PPARG rs796313 and rs17793951 was associated with a 2.85-fold increased risk of low responsiveness to influenza vaccine. Conclusion: Our study identified that PPARG rs17793951 variants were significantly associated with the immune response to influenza vaccine.